Предмет: Алгебра,
автор: захар555
6. Разложите на множители: b3 - 4b2 + 4b.
Разложите на множители: (z + 3)2 + x2 - x (2z + 6) .
Ответы
Автор ответа:
0
b³ - 4b² + 4b= b(b²-4b+4)= b(b-2)²= b(b-2)(b-2)
(z + 3)²+ x²- x(2z + 6)=
z²+6z+9+x²-2xz-6x=
z²+x²+3(2z+3)-2x(z+3) не знаю как дальше, извини
(z + 3)²+ x²- x(2z + 6)=
z²+6z+9+x²-2xz-6x=
z²+x²+3(2z+3)-2x(z+3) не знаю как дальше, извини
Похожие вопросы
Предмет: Обществознание,
автор: zyukovauv
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: svetikserj
Предмет: Алгебра,
автор: adiletorken